Benefits and challenges of transitioning preterm infants to at-breast feedings - Buckley Kathleen M; Charles Gloria E (BMC, 2006)
Abstract Upon hospital discharge it is not unusual for mothers of preterm infants to continue to meet all or most of their infants' nutritional needs through bottle feedings of expressed breast milk (EBM) because of infants' physiological immaturity and maternal concerns with an inadequacy of milk supply. Although for some mothers the challenge of transitioning the infant to feeding at the breast may be beyond their ability and resources, for others it appears to be based on a conscious choice. Mothers are often unaware of the advantages of breastfeeding at the breast. The purpose of this article is to examine some of the factors that may contribute to the inability and resistance of mothers to transition their preterm infants, and to report on the potential short and long-term advantages associated with feeding at the breast as opposed to feeding bottles of EBM.